THEOLOGY OF NATION’S INTEGRATION FOR MALUKU SOCIETY POST-INDONESIAN INDEPENDENCE REVOLUTION, 1945-1949 - Johan Robert Saimima; Henky Herzon Hetharia; Dave Stenly Nenkeula; Rouli Retta Trifena Sinaga (Manna Rafflesia)
In the era of the independence revolution, 1945-1949, Maluku society was polarized, namely groups of people affiliated with the Partai Timur Besar (PTB) which was against Indonesian independence and the Partai Indonesia Merdeka (PIM) that was pro-independence. This study uses qualitative research with descriptive analysis based on historical research methods, namely: searching for historical sources (heuristics), determining source criticism, carrying out interpretations, and carrying out historical writing (historiography). The research results shows that the PTB group did not support independence and wanted Maluku to be separated from the State of Indonesia. PTB’s wishes were blocked by the pro-Indonesian PIM group. PIM moved to defend Indonesia’s national identity from attacks by PTB loyalists. This political upheaval had an impact on the unity of Indonesian society in Maluku. The people of Maluku who are pro for Indonesian independence are struggling amid pressure from groups against independent Indonesia to ensure that Maluku remains part of the Republic of Indonesia. Then, the theology of nation’s integration based on nationalism perspective becomes an offer for a vision that unites Indonesia’s diverse society, while also being based on humanity and solidarity.